Developing a Preliminary Learning Syntax Based on Learners' Needs: A Plurilingual Blended Learning Model for Functional English Literacy - Hardianti; Nurhaida Lakuana; ST Marhana Rullu; Zeni Afriani Zainudin; Afifah Mardhiyyah (STIT Buntet Pesantren Cirebon, 2026)
Non-formal education in Indonesia plays a strategic role in providing alternative and complementary learning pathways; however, learners in Community Learning Centers (PKBM) remain disadvantaged due to limited functional English and digital literacy. Existing studies on blended learning often prioritize technological integration without addressing learners’ plurilingual realities, while English instruction in non-formal settings frequently replicates formal education patterns, resulting in low participation and limited skill relevance. This study addresses this gap by proposing a plurilingual blended learning model grounded in learners’ actual needs. A qualitative needs analysis was conducted involving 18 participants (12 learners, 3 tutors, and 3 program coordinators) in a non-formal education setting. Data were collected through semi-structured interviews, field observations, and they were analyzed using thematic coding to identify recurring linguistic, pedagogical, and contextual patterns. Findings reveal three core learner needs: (1) context-based communicative tasks that do not rely on partial instruction; (2) scaffolded digital support; and (3) flexible language use integrating local and global languages. These informed the development of a six-phase preliminary learning syntax: learners’ language repertoires activation, plurilingual input, collaborative meaning-making, functional English transformation, functional literacy practice, and plurilingual reflection and digital reinforcement. The study is limited by its small, context-specific sample, affecting generalizability. Nonetheless, it offers practical implications for designing adaptive, inclusive learning models in non-formal education. Future research should test the model’s effectiveness through experimental and larger-scale studies.